Antioxidant Activity of Chitooligosaccharides Produced by Chitinase Extracted from two Weeks Seedlings of Samanca saman (Jacq) Merr. - Kaomek, Mana (Journal of Applied Research on Science and Technology (JARST), 2021)
This research was to study the antioxidant activity of chitooligosaccharides from two weeks seedlings of Samanca saman (Jacq) Merr. produced by chitinase with extraction of 0.1 molar acetate buffer at pH 3.5 was investigated in this work. It was found that chitooligosaccharides obtained from hydrolysis of 1 percent of colloidal chitin in 0.1 molar acetate buffer pH 3.5 using chitinase extracted from two weeks seedlings of Samanca saman (Jacq) Merr. at 0.5 hour digestion, chitooligosaccharides were produced from hydrolysis of 1 percent of colloidal chitin in 0.1 molar acetate buffer pH 3.5 utilizing chitinase isolated from two weeks seedlings of Samanca saman (Jacq) Merr. It comprises acetylglucosamine as well as (GlcNAc)2, (GlcNAc)3, (GlcNAc)4, (GlcNAc)5, and (GlcNAc)6 of chitooligosaccharides. The small molecules of (GlcNAc)1, (GlcNAc)2 and (GlcNAc)3 increased with 1 hour, 2 hours and 4 hours of curing time, the small molecules of (GlcNAc)1, (GlcNAc)2, and (GlcNAc)3 increased, whereas the large molecules of (GlcNAc)4, (GlcNAc)5 and (GlcNAc)6 decreased. The large molecules of (GlcNAc)4 changed to (GlcNAc)2 + (GlcNAc)2 and (GlcNAc)1 + (GlcNAc)3, (GlcNAc)5 changed to (GlcNAc)2 + (GlcNAc)3 and (GlcNAc)1 + (GlcNAc)4, (GlcNAc)6 changed to (GlcNAc)3 + (GlcNAc)3, (GlcNAc)2 + (GlcNAc)4 and (GlcNAc)1 and (GlcNAc)5. Chitooligosaccharides obtained from the use of every curing time to digest which have antioxidant activity better than butylated hydroxyl toluene (BHT) standard. The EC50 of 0.5 hour, 1 hour, 2 hours and 4 hours incubation were 1.01 0.1, 1.07 0.1, 1.12 0.1 and 1.18 0.1 µg/mL, respectively, which less than the EC50 of BHT standard of 1.34 0.1 µg/mL. The large molecules of chitooligosaccharides from shorter curing time (0.5 hour) have more antioxidant activity than small molecules from longer curing time (1 hour, 2 hours and 4 hours).